2016
DOI: 10.3346/jkms.2016.31.10.1664
|View full text |Cite
|
Sign up to set email alerts
|

Hirayama Disease with Proximal Involvement

Abstract: Hirayama disease is a slowly progressing benign motor neuron disease that affects the distal upper limb. A 29-year-old man visited the hospital with a 1-year history of weakened left proximal upper limb. He was diagnosed with Hirayama disease 9 years ago, while there was no further progression of the muscle weakness afterward. Atrophy and weakness was detected in proximal upper limb muscles. Magnetic resonance imaging and somatosensory evoked potentials were normal. Needle electromyography showed abnormal find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, 8 years later, he visited a hospital with relapsed unilateral weakness of proximal upper limb. His neutral position neck MRI findings showed no abnormal cervical vertebrae, and anterior shifting of the spinal cord during cervical vertebrae flexion was not observed 7) . This is consistent with the report which showed that abnormal MRI results are lessened or even disappear naturally 12) .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, 8 years later, he visited a hospital with relapsed unilateral weakness of proximal upper limb. His neutral position neck MRI findings showed no abnormal cervical vertebrae, and anterior shifting of the spinal cord during cervical vertebrae flexion was not observed 7) . This is consistent with the report which showed that abnormal MRI results are lessened or even disappear naturally 12) .…”
Section: Discussionmentioning
confidence: 87%
“…In Korea, six cases have been reported from 2004 to 2016, but there was no nationwide survey. They were all male between ages from 15 to 29, and some of them showed atypical clinical features 7,[16][17][18][19] . Four of the six patients showed involvement of proximal upper extremities, while the other two showed involvement of distal upper extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Ammendola et al ., in a study of three cases, did not show statistically significant differences for F-wave, SSEPs, and motor evoked potentials in standard conditions and during neck flexion both in HD patients and controls, suggesting that some cases of a complex disorder like HD might have a pathogenetic mechanism different from “flexion myelopathy.”[ 2 ] We evaluated the changes in N9–N20 interpeak latencies during neutral in all patients and flexed neck positions in three cases, without significant changes, as published in other reports. [ 1 , 2 , 11 , 17 , 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive microtraumas to the anterior horn motor neurons during neck exion are now considered as the possible pathogenesis of the disorder [10,16]. In view of this, cervical collars, which could restrain the neck exion, have been widely used in the treatment of HD and brought out favorable outcomes [4]. Although cervical collars are regarded as the mainstay of the treatment, surgical interventions are well established as an alternative for HD patients who are in advanced conditions, irresponsive to conservative treatment, or intolerant to cervical collars [5,8,12,15].…”
Section: Introductionmentioning
confidence: 99%